Why Does a Growth Mindset Intervention Impact Achievement Differently across Secondary Schools? Unpacking the Causal Mediation Mechanism from a National Multisite Randomized Experiment. Issue 3 (3rd July 2021) - Qin, Xu; Wormington, Stephanie; Guzman-Alvarez, Alberto; Wang, Ming-Te
Abstract: The growth mindset or the belief that intelligence is malleable has garnered significant attention for its positive association with academic success. Several recent randomized trials, including the National Study of Learning Mindsets (NSLM), have been conducted to understand why, for whom, and under what contexts a growth mindset intervention can promote beneficial achievement outcomes during critical educational transitions. Prior research suggests that the NSLM intervention was particularly effective in improving low-achieving 9th graders' GPA, while the impact varied across schools. In this study, we investigated the underlying causal mediation mechanism that might explain this impact and how the mechanism varied across different types of schools. By extending a recently developed weighting method for multisite causal mediation analysis, the analysis enhances the external and internal validity of the results. We found that challenge-seeking behavior played a significant mediating role, only in medium-achieving schools, which may partly explain the reason why the intervention worked differently across schools. We conclude by discussing implications for designing interventions that not only promote students' growth mindsets but also foster supportive learning environments under different school contexts.